Tradisi Upacara Cafi Sari Masyarakat Suku Mbojo: Kajian Folklore - Sukarismanti Sukarismanti (Universitas Pahlawan Tuanku Tambusai, 2022)
Humans are creators of cultural products to be passed on to the next generation. One of the cultural products created by humans is the Cafi Sari tradition. This tradition is carried out from generation to generation. However, nowadays, many people do not know the meaning and function of the Cafi Sari ceremony tradition, which they still preserve. Therefore, this study aims to explore the meaning and function of the cafi sari tradition to provide understanding to the millennial community as heirs of the tradition. This study uses a phenomenological approach to understand the meaning of an event and human interaction in certain situations. Then, the theory used in this research is folklore theory. Data collection techniques use the methods of observation, interviews, and documentation. The results showed that the Cafi sari ceremony was performed when a new mother gave birth. It starts with the ritual of Cafi sari, or cleaning the sari or floor after 7 days of giving birth. The meaning contained in this ritual is a clean and healthy life behaviour starting from food, drink, environment, body hygiene, and the right goal in living the life of the world to the hereafter. In contrast, the Cafi Sari ceremony tradition functions as a ritual function, social function, religious function, and educational function. Keywords : Tradition of Ceremony, Folklore, Cafi Sari